Measuring Home Care Caseloads: Development of the Caseload Intensity Tool. (November 2014) - Collister, Barbara; Slauenwhite, Carol Ann; Fraser, Kimberly D.; Swanson, Signe; Fong, Andrew
In response to caseloads that are increasing in numbers and acuity, Alberta Health Services developed the Caseload Intensity Tool (CIT). The development and testing process led to a valid and reliable tool that connects client clinical condition to clinician response. The CIT allows clinicians to discriminate between levels of client intensity quickly and accurately. The scores for each client are summarized first into a client intensity scale and then a caseload intensity scale. The CIT can facilitate caseload management including matching client needs to resources and improving staff resource management, for example, equitable caseloads. There is potential for the tool to validate the relatively invisible work of case managers making it understandable, measurable, and defensible during times of rising costs and budget restraint.